ANALISIS PEMANFAATAN WEBSITE JAKARTA.GO.ID DALAM MENINGKATKAN GOOD GOVERNANCE DI DKI JAKARTA TAHUN 2021 - Chissa Putri Raharningtyas (PANDITA : Interdisciplinary Journal of Public Affairs, 2021)
The development of Information and Communication Technology (ICT) has a significant impact on human life. Recently, the term electronic-based government or known as e-Government, has emerged. One of the manifestations in the implementation of e-Government is the creation of a local government website. Therefore, this study aims to find out how the use of DKI Jakarta official website jakarta.go.id. This study used a qualitative method with a descriptive approach. This study used the principal of Good Governance theory. The results of the study show that the use of DKI Jakarta official website jakarta.go.id has been running quite well, jakarta.go.id website has been useful for the wider community. The supporting factors for the use of the jakarta.go.id website are technologies and resources, while the inhibiting factor for the use of jakarta.go.id website is coordination.